2014
DOI: 10.1002/anie.201407083
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Highly Selective CH Functionalization of Structurally Diverse Ethers

Abstract: A trityl ion mediated C-H functionalization of ethers with a wide range of nucleophiles at ambient temperature has been developed. The reaction displays high chemoselectivity and good functional group tolerance. The protocol also exhibits excellent regio- and diastereoselectivities for the unsymmetric ethers, thus stereoselectively generating highly functionalized disubstituted 2,5-trans tetrahydrofurans (THF), 2,6-trans tetrahydropyrans (THP), 2,6-trans dihydropyrans (DHP), and 1,3-trans isochromans, and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 88 publications
0
38
0
1
Order By: Relevance
“…In this context, significant success was recently achieved by MacMillan and Jin, who developed an efficient photoredox‐mediated α‐arylation of both cyclic and acyclic ethers with electron‐deficient heteroarenes (Scheme , a) . Liu and co‐workers showed that the reactivity of the trityl ion can be successfully tuned to promote chemoselective C–H functionalization of various cyclic ethers (Scheme , b)[8a] and also disclosed effective, oxidative cross‐dehydrogenative coupling protocols for chromenes, benzylic ethers, and benzopyran. An efficient palladium‐catalyzed stereoselective arylation protocol at the unactivated 3‐position of THP was recently described by Affron and Bull (Scheme , c) …”
Section: Introductionmentioning
confidence: 99%
“…In this context, significant success was recently achieved by MacMillan and Jin, who developed an efficient photoredox‐mediated α‐arylation of both cyclic and acyclic ethers with electron‐deficient heteroarenes (Scheme , a) . Liu and co‐workers showed that the reactivity of the trityl ion can be successfully tuned to promote chemoselective C–H functionalization of various cyclic ethers (Scheme , b)[8a] and also disclosed effective, oxidative cross‐dehydrogenative coupling protocols for chromenes, benzylic ethers, and benzopyran. An efficient palladium‐catalyzed stereoselective arylation protocol at the unactivated 3‐position of THP was recently described by Affron and Bull (Scheme , c) …”
Section: Introductionmentioning
confidence: 99%
“…Later, Pan’s group demonstrated an iron‐catalyzed esterification of inactive C( sp 3 )H bonds in 1,4‐dioxane with carboxylic acids 10b. Very recently, Liu’s group reported the selective direct construction of diverse α‐functionalized ethers by use of the trityl ion and a Lewis acid catalyst at ambient temperature 10c…”
Section: Introductionmentioning
confidence: 99%
“…Diastereoselective zinc-catalyzed alkynylation of α-bromo oxocarbenium ions to synthesize trans-α-alkynyl-β-halo pyran and furan derivatives is known [47]. Lastly, C-H functionalization of THF derivatives has been achieved using organotrifluoroborates and trityl ions [48]. While a range of methodologies exists for the preparation of 2-alkenyl and 2-alkynyl tetrahydrofurans, the necessity to use stoichiometric amounts of a Lewis acid, expensive metal catalysts and sensitive reagents hinder the practicality of these approaches.…”
Section: Resultsmentioning
confidence: 99%